The effect of depth of the trap zone of an end release avalanche on the depletion of ore loss - Xiaoyu Wu; Nan Zhang; Xiaowei Wu (Scientific Reports)
Abstract In sublevel caving without sill pillar, the shape of caving body is an important factor affecting the ore drawing effect. The depth of collapse area is one of the important parameters of collapse body shape, but there was no research on the influence of the depth of collapse area on reducing ore loss and dilution in the past. This paper puts forward the problem of the influence of the depth of the collapse area on ore loss and dilution. A large scale model of end ore drawing is developed, and matching positioning films and coded color marker particles are made. The specific experimental scheme has been determined, and experiments on collapse collapse area at different depths have been carried out. Each group of experiments has carried out ore rock filling, symbolic particle placement, and ore drawing experiments according to the experimental scheme. In the process of ore drawing, the sorted ore and rock data, recovered landmark particles and corresponding codes and drawing time are collected. The following achievements have been made: (1) The depth of the collapse area affects the formation of the draw out body and has a greater impact on the ore loss and dilution. As the depth of the collapse area deepens, the ore loss rate increases and the ore dilution rate changes slightly. When the depth of collapse body collapse area is 0 mm, the ore loss rate is 29.73%, and the dilution rate is 20.60%. The ore loss rate is the smallest, and the dilution rate is relatively low. (2) When the cut-off grade is 20%, the amount of pure ore recovered in each group of experiments is about twice the amount of pure ore in the pure ore stage with the change of the depth of the collapse body collapse area. (3) During end ore drawing, the closer the pole position of the subsidence area is to the flow axis, the faster the pole descending speed, the expansion speed of the waste rock and ore contact surface, and the ore dilution speed are.